Modeling of reservoir temperature upon preheating in SAGD wells considering phase change of bitumen. (December 2019) - Gao, Yanfang; Chen, Mian; Lin, Botao; Jin, Yan
Highlights: Properties of oil sands and crude bitumen in Karamay and Alberta are investigated. Heat transfer considering phase change is proposed to describe process of preheating. Temperature propagation with latent heat is analytically and numerically predicted. Abstract: Steam circulation prior to production is usually employed to establish inter-well thermal communication and create an expected initial steam chamber in the process of bitumen recovery using steam assisted gravity drainage (SAGD). To realistically evaluate the efficiency of steam circulation, and to find the indicator for terminating the steam circulation and switching to SAGD production, modeling of the temperature propagation considering the bitumen-rich oil sand reservoir properties and oilfield operations is required. This study proposed two new modified methodologies, including an analytical model as well as a numerical model, in which the latent heat effect caused by the phase change of bitumen was involved for thermo-phase change coupled analyses. The modeling was conducted for a real SAGD steam circulation project in an oilfield located in Karamay, northwest of China, using oilfield operation parameters and thermo-dynamical properties obtained from laboratory tests. The models can predict the temperature propagation and bitumen phase change behavior in the domain encompassing dual wells. In general, the predicted results obtained from both analytical and numerical approaches agree well with those in published articles in terms of the cooling time derived from temperature falloff tests and inter-well midpoint temperature. The modeling draws major conclusions that the temperature drops rapidly with the distance to wellbore in the fusion zone, but decreases slowly in the solid zone. The heat flux on wellbore exhibits an exponential reduction in the beginning, but ultimately tends to be a constant. The moving speed of phase change interface decreases with injection time, and finally increases up to only a short distance. The inter-well midpoint temperature is heated to exceed the threshold temperature, and the whole inter-well area is ultimately occupied by the fusion zone. These findings not only can provide a criterion for evaluating the efficiency of steam circulation and an indicator for terminating the steam circulation and switching to production, but also the approaches proposed may be used to analyze these heat injection and phase change problems occurring in other types of oil and gas-rich reservoirs like the natural gas hydrate formation.